Use of Active and Passive Verb Forms in Papers from the Field of Chemical Engineering - Tomas Bakalar; Magdalena Razusova; Henrieta Pavolova; Barbara Hlavnova (Communications - Scientific letters of the University of Zilina, 2014)
The paper deals with use of active and passive verb forms in journal articles from the field of chemical engineering with focus on heavy metal ions removal from water. Three hypotheses about use of passive and active voice were formed and tested on six scientific journal papers in the above mentioned field – three experimental and three theoretical. The data were gathered using a comparative analysis of active and passive verb forms with a share of statistical analyses. Hypothesis 1 “In scientific papers from the field of chemical engineering passive voice is more frequent than the active voice.” is not valid as the active verb forms outnumber the passive verb forms though not significantly. Hypothesis 2 “Passive voice is much more common in Methods and Discussion sections than in the Introduction or Results sections.” can only be applied to experimental papers and is valid as the passive verb forms outnumber the active ones in the particular sections. Hypothesis 3 “There is no difference in usage of passive and active voice in theoretical and experimental scientific papers.” is not valid as in experimental papers the passive verb forms outnumber the active ones, on the other hand, in theoretical papers this statement does not apply.